POTENSI PRODUK KARET PERKEBUNAN RENTENG PTPN XII DI JEMBER DALAM KONTRIBUSI TERHADAP FLUKTUASI KARET JAWA TIMUR - Mochammad Nasirudin; Mohammad Wimbo Raksagiri (UPT Penerbitan Universitas Jember)
Based on data from the FAO, Indonesia is the second producer of rubber in the world after Thailand. Although Indonesia is at the second position as the world rubber producing countries, Indonesia will be in the fifth position in rubber productivity. For East Java best rubber products rubber sheet categories of Jember with the brand